Trends in Incidence of Neonatal Sepsis and Antibiotic Susceptibility of Causative Agents in Two Neonatal Intensive Care Units in Tehran, I.R Iran - Afsharpaiman, Shahla (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Neonatal sepsis is a worldwide problem that presents a management challenge to care groups for neonates and infants. Early diagnosis and management can considerably decrease the risk of sepsis, and improve the outcome. AIM: The aim of the present study was to determine the incidence, causative pathogens, and the antibiotic sensitivity pattern for neonatal sepsis in Iran. MATERIALS AND METHODS: A historical cohort study was conducted on 84 patients with neonatal sepsis who were admitted to the neonatal intensive care unit (NICU) wards of Baqiyatallah and Najmieh University hospitals in Tehran, between 2003 and 2006. Clinical, demographic and laboratory data was collected from medical records. RESULTS: Among all the comprised neonates, 44 patients were diagnosed with early-onset sepsis, 23 cases with late-onset sepsis and others with nosocomial sepsis. The most common isolated pathogen in all groups was Enterobacter, and was responsible for 31.4%, 47.8% and 41.2% of the episodes of sepsis, according to the sepsis type mentioned above, respectively. Susceptibility of common sepsis related pathogens to imipenem and gentamycin gradually reduced over the years between 2003 and 2006. Total mortality and morbidity rates due to neonatal sepsis were estimated at 27.4% and 89.3%, respectively. Mortality following sepsis was found more in boys (Odds Ratio (OR)=4.897, Conifdence Interval (CI)=95%, P=0.031), and those with low birth weight (OR=4.406, CI: 95%, P=0.011). Higher sepsis related co-morbidity was found in neonates following cesarean delivery (OR=6.280, CI: 95%, P=0.025). CONCLUSION: It seems that the mortality rate in this study was lower than similar studies in Iran and other developing countries. This difference between the mortality rates of the centers in our study and others could be due to the high occurrence of Enterobacter infections in the latter and also high resistance of these pathogens to commonly used antibiotics such as β-lactams and aminoglycosides reported in other studies.